ASESMEN PSIKOLOGI DAN PELATIHAN BAGI PENDAMPING ANAK DAN REMAJA DARI LINGKUNGAN BERISIKO - Sari, Diana Permata; Astuti, Ratri Sunar; Etikawati, Agnes Indar; Mulyatno, C. B.; Sianipar, Cecilia Paulina (Universitas Sanata Dharma, 2024)
Children at risk are children who are vulnerable to losing their rights due to certain conditions in their environment or certain situations in their lives. Children at risk need to receive appropriate assistance to develop adaptive behavior. To provide appropriate assistance, a psychological assessment is needed because most children are at risk of experiencing psychological problems. The results of the assessment showed that forms of psychological problems were found, including difficulty regulating emotions, feeling insecure, negative self-concept, feeling rejected by the environment, lack of familiarity with rules and manners, not knowing what is right and wrong, committing acts of aggressiveness, being undisciplined, experiencing learning difficulties, lack of social skills. Based on these findings, training for at-risk children's companions is provided. There are five training topics, namely creating a supportive and empathetic atmosphere, teaching to act with conscience, basic counseling skills, emotional regulation, and developing social and communication skills in children. The results of the training can provide additional knowledge and skills to caregivers and companions of children at risk at the Dream House.